PENGARUH PENAGIHAN AKTIF, KEMAMPUAN PROFESIONAL, DAN PENGALAMAN FISKUS DALAM PENCAIRAN TUNGGAKAN PAJAK - Sabaruddin Sabaruddin; Tri Wahyuni (Jurnal Akuntansi Bisnis, 2017)
This study aims to identify and acquire empirical evidence of how the influence of active addiction, professional skills and experience in the tax authorities of tax arrears. The population used in this study is the tax on KPP Pratama Jakarta Cilandak. The data obtained in this study through questionnaires completed by a sample of 55 tax authorities. The analysis method used in this research is multiple linear regression. Based on the results of research conducted in the statistical analysis showed that the drug is active in influencing the disbursement of tax arrears, as a result of the t test statistics show that t> t (3,385> 2,004) and significantly greater levels of the real level (0.001 <0.05). The variable does not affect the ability of a professional in the disbursement of tax arrears, as a result of the t test statistics show that t <t (- 0,062 <2,004) and significantly greater levels of the real level (0.951> 0.05). And experience variables affect the tax authorities in tax arrears, as a result of the t test statistics show that t> t (2,358> 2,004) and significantly greater levels of the real level (0.022 <0.05). The simultaneous collection of active, professional skills and experience in the tax effect of tax arrears, because test results showed that f t> t (12,895> 2,786) and significantly greater levels of the real level (0.000 <0.05). Keywords: Active Billing, Professional Capability, Experience tax authorities,and tax arrears